Treatment for Severe Class II Open Bite Using a Bonded Hyrax Expander, IZC Mini-Implants, and MEAW Technique in an Adolescent Patient - Mohammad Farahani; Reza Morvaridi Farimani; Fatemeh Eskandarloo (Case Reports in Dentistry)
This case report describes the successful 3D treatment of a patient with a narrow maxilla and a severe class II open bite using a combination of a bonded hyrax expander, infrazygomatic crest mini-implants, and the multiloop edgewise arch-wire (MEAW) technique. A 14-year-old female with a thumb-sucking habit in childhood, presented with a severe open bite, a convex profile, and an obtuse nasolabial angle. Diagnosis revealed a skeletal Class II open bite with moderate crowding in the maxillary and mild crowding in the mandibular arch. Treatment objectives included eliminating the open bite, achieving normal overbite and overjet, and improving upper incisor visibility. Treatment involved the use of a bonded rapid palatal expansion device, mini-implants for maxillary intrusion, fixed appliances, vertical elastics, and a MEAW. Treatment results showed resolution of the open bite, improvement in overbite and overjet, achievement of Class I molar and canine relationships, and improved upper incisors visibility. Fixed appliances were used for the whole 22-month therapy period, and post-treatment records demonstrated that the treatment’s objectives were met.